Study on the License Mode of Value-Added Exploitation of Public Sector information - Haiying Hua; Shuren Zhu (Universitas Islam Sultan Agung, 2013)
How to license PSI (public sector information) to those commercial reusers has become so urgent and important issue. The paper discussed the different license mode of value-added exploitation of Public Sector Information in UK and United States. Based on the investigation and comparison, the paper proposed some valuable suggestions on the construction of license mode of value-added exploitation of PSI in China: A clear attribution of property of public sector information and a clear range of Public sector information that can be accessed and be commercial reused and exploited; A diversification license based on clear classification of Public Sector Information; To establish unified management institute and supervisory body and so on.